2009
DOI: 10.1021/ac901258g
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantitation of IgG 1 Hinge Aspartate Isomerization: A Rapid Degradation in Stressed Stability Studies

Abstract: In biopharmaceutical process development, it is desirable to identify sites of covalent degradations to ensure product consistency. One characterization method used for therapeutic immunoglobulin gamma (IgG) 1 antibodies is limited LysC proteolysis followed by reversed-phase LC/MS. Limited LysC proteolysis leads to high efficiency cleavage at the C-terminal side of the hinge lysine 222 residue, generating Fab and Fc fragments. In this report, we show that IgG 1 samples incubated under mildly acidic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…To this end we first obtained a uniform data set that contains residue-specific quantitative data on antibody degradation products. Where available, these detected modifications are in accordance with known hotspot information from published data [11], [12], [54], [91]. The pH was kept constant at 6.0 during forced degradation and sample preparation to detect the succinimide intermediate that quickly hydrolyzes at alkaline pH, Asp isomerization, which occurs mainly at slightly acidic pH, and Asn deamidation without method-induced deamidation events.…”
Section: Discussionsupporting
confidence: 55%
“…To this end we first obtained a uniform data set that contains residue-specific quantitative data on antibody degradation products. Where available, these detected modifications are in accordance with known hotspot information from published data [11], [12], [54], [91]. The pH was kept constant at 6.0 during forced degradation and sample preparation to detect the succinimide intermediate that quickly hydrolyzes at alkaline pH, Asp isomerization, which occurs mainly at slightly acidic pH, and Asn deamidation without method-induced deamidation events.…”
Section: Discussionsupporting
confidence: 55%
“…Although isomerization of aspartic or glutamic acid residues does not directly result in generation of charged species, it could indirectly affect surface charge distribution by inducing local conformational perturbation resulting in solvent exposure of neighboring residues Hambly et al have shown isomerization of Asp223 in the hinge region to be the fastest degradation in another IgG1 (40). They pointed that hinge tryptic peptide SCD 223 K is a polar peptide that elutes early in the void volume in reduced-alkylated reversed phase chromatogram in alkylated form (iodoacetic acid alkylation, +58 Da), and therefore difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Protein therapeutics are inherently structurally complex biological drugs whose active components are not a single, well-defined molecule, but a mixture of similar molecules which can differ by type and extent of post-translational modification, 15 chemical modifications, 611 and three dimensional conformations. 12,13 In addition, batch to batch variation of active components and production impurities can further complicate defining of the analytical characteristics of a protein drug.…”
Section: Introductionmentioning
confidence: 99%